Annual compilation of wrestling research 2017 - Curby, D. (International Network of Wrestling Researchers, 2018)
The Annual Compilation of Wrestling Research 2017 is compilation of published wrestling-related research during 2017 is provided by the International Network of Wrestling Researchers (INWR). The INWR is the largest scientific support group for a sport in the world! Our group has grown to over 400 academics, scientists, doctors and wrestling professionals, from 80 countries who are involved with the sport of wrestling. (www.inwr-wrestling.com) Our Mission Statement is: The International Network of Wrestling Researchers (INWR) seeks to facilitate the development of wrestling around the world by drawing all wrestling sport science professionals together, in a manner that through our international and intercultural cooperation we are empowered to support the development of wrestling with our research and educational programs